The Influence of the Use of the Approach of Blended Learning Model Rotation Based Moodle on Motivation and Cognitive Abilities of Students in the Subjects of Physics - Ulan Dari; A Halim; S. Ilyas (Jurnal Penelitian Pendidikan IPA, 2022)
Students' motivation to learn is the main aspect to achieve student success. Based on the results of observation and interview, the learning motivation of students in SMA Negeri 2 Kutacane is still relatively less, so the impact on the low cognitive ability of the students. The purpose of this study is to see the influence of the approach blended learning type station rotation on differences in motivation and cognitive abilities after the study. This research use approach uses quasi-experiments design pretest-posttest control group design. The population of this research is all students of class XI, the sample taken is of class XI IPA 2 as the experimental class and XI IPA 3 as the control class. Using a data collection instrument sheet, questionnaires, and interviews to measure the motivation to learn and use the instrument on a test to measure the cognitive abilities of the students. The results of data analysis using t-test (independent sample t-test) show the differences in motivation and cognitive abilities of students with a significance of 0.000Â <Â 0.05 means there is a significant difference between the motivation and ability of cognitive control and experimental classes. Therefore, it can be concluded that there is an influence of the use of the approach blended learning type station rotation motivation and cognitive abilities of the students.